Factors influencing day-to-day planning: Protest - cooperation - indifference? - Christian Lamker ("All change please!": Challenges and opportunities of the energy transition, 2022)
Current planning debates are characterised by the tension between political and societal goals on the one hand and questions of local implementation on the other. The general public and individual citizens are core elements of any planning process, with their level of involvement in day-to-day planning ranging from protests to cooperation to indifference. There are gaps in our knowledge about which factors affect planning stipulations in everyday practice. Using empirical data gathered in basic research on German municipalities of all sizes, this article develops an exploratory comparison of the planning challenges posed by the energy transition and the integration of major accident prevention in urban land-use planning. It identifies differences, the significance of internal and external influencing factors, and starting points to pave the way to better cooperation in daily planning activities.
urn:nbn:de:0156-41340577; hdl:10419/250056; https://econpapers.repec.org/RePEc:zbw:arlabe:32
Keywords: 710; urban land-use planning; civic participation; energy transition; planning practice; major accident prevention